AN EXAMINING OF JEPHTHAH’S VOW ACCORDING NARRATIVE RESEARCH - Daniel Lindung Adiatma; Sutrisno Sutrisno (Scriptura Indonesia, 2021)
The book of Judges is great historiography of the Old Testament. This book is composed of many rhetorical devices in the form of narrative. Scholar, pastor, professor etc pay attention to elaborate theological issue of this book. Some of academic journal elaborate about ethical issue about Jephthah’s vow. Common interpretation used topical approach to examine ethical issue. The main problem to interpret Jephthah vow is that many interpreters did not used narrative approach, so that they have lost the writer emphasis. This article aims to examine Jephthah’s vow according narrative approaches. Some of interpretation book of the Old Testament, especially commentary on Judges 11:29-40 forget narrative approach as literary that writer used. Literary approach of the Judges 11:29-40 presents the properly approach to produce properly theological interpretation. This article elaborating each plot of Judges 11:29-40 to find the motive of narrator. The interpretation is according the structure of narrative text produce the precise and clear interpretation. The writer striving to consistent with an interpretation rule in examine each part of the passage. Therefore, this article is an academic writing that gives rich insights.